PENGELOLAAN PERTANIAN LAHAN KERING TANAMAN PADI UNTUK MENGIDENTIFIKASI KETAHANAN PANGAN DI DESA LETBAUN KECAMATAN SEMAU - Kollan, Oktobira; Hasan, Muhammad Husain; Manek, Agustinus Hale (Universitas Nusa Cendana, 2024)
Letbaun Village has productive land to be processed into agricultural land. This study aims to determine (1) the characteristics of dry land management for rice plants to identify food security (2) the level of agricultural production (3) the income of the people of Letbaun village, especially rice management and (4) the contribution of rice farmers on food security in Letbaun Village, Semau District. The subjects of this research were 20 people, all of whom were rice farmers in Letbaun village. The research method used was descriptive qualitative. The results of this study indicate that the agricultural management system in Letbaun Village is still traditional and has a unique character formed by limited 120 kg and the highest is 800 kg of rice. In supporting sustainable food security, Letbaun Village farmers are supposed to contribution to Letbaun Village, but with low rice income, farmers are unable to make that contribution. It can be concluded that food security in Letbaun Village is low and the main factor is limited water, where water is one of the main factors that contributing to the low level of food security in Letbaun Village.